Susceptibility of strong biofilm-producing uroisolates in planktonic state vs. Biofilm growth mode. - Labachevska Gjatovska, Liljana; Pavlovska, Kristina; Jankoska, G; Bojan Labachevski (Macedonian Association of Anatomists and Morphologists (MAAM), 2021)
Introduction: Biofilms are defined as functional consortiums of microorganisms, attached to a surface, enclosed in self-produced hydrated polymeric matrix. Between microorganisms in biofilm and free floating microorganisms of the same species there are essential differences regarding: specific gene expression, ability for intercellular communication via biochemical signaling molecules, antimicrobial resistance. These biofilm features play a key role in the development of chronic and antibiotics tolerant infections. The ability of uropathogens to cause relapses of UTI directly correlates with their genetic capability for biofilm production on catheter surfaces or uroepithelium and with the innate recalcitrance to treatment of the biofilm itself. Objective: To investigate the differences in pathogens resistance in relation to biofilm expression phenotype by comparing the antibiotic susceptibility of sessile cells and their planktonic counterpart, for biofilm forming bacteria isolated from patients with UTI. Materials and methods: The study included 120 urine samples from outpatients, from both genders, over 18 years of age, with suspected UTI, referred for microbiological examination of urine at the Institute of microbiology and parasitology, Medical faculty, Skopje. A total number of 80 bacterial species, isolated in monobacterial culture were examined for biofilm production. For biofilm cultivation and biofilm biomass determination, adherence assay on 96-well microtitre plate and semi-quantitative spectrophotometric method were used. For 25 selected strong biofilm producers, antibiotic susceptibility to ciprofloxacin and sulfametoxasole trimetoprime of planktonic cells was tested by microdilution assay and compared with the antimicrobial sensitivity of bacterial biofilms (performed with the Calgary Biofilm Device) Results: Distribution of susceptibilities, regarding the frequency of the sensitive, intermediate and resistant bacteria showed statistically significant difference in the antibiotic susceptibility of planktonic cells vs. their sessile counterparts (p<0.01) / Fisher ́s Exact p. Results showed that bacteria are more resistant in biofilm communities as compared to planktonic form by comparison of MIC & MBEC assay. Conclusion: Attached bacterial communities (biofilms) present with an innate deficit of antibiotic susceptibility not registered in the same bacteria grown at planktonic state. Minimal biofilm eradication concentrations, determined applying the Calgary Biofilm Device, reveal that treatment of biofilms requires 20 to 1,200 times concentrations of a certain antibiotic to achieve the desired antimicrobial effect compared with planktonic cells of the same organisms which urges future changes in the conventional therapeutical approach.
Keywords: biofilm; urinary infections; resistant